Within reach : my Everest story - Pfetzer, Mark.; Galvin, Jack. (New York : scholastic, 1999)
The author describes how he spent his teenage years climbing mountains in the United States, South America, Africa, and Asia, with an emphasis on his two expeditions up Mount Everest.
G8
Keywords: Pfetzer, Mark -- Juvenile literature; Pfetzer, Mark; Mountaineers -- United States -- Biography -- Juvenile literature; Mountaineering -- Everest, Mount (China and Nepal) -- Juvenile literature; Youths' writings, American; Mountaineers; Youths' writings; Everest, Mount (China and Nepal)